Early‐stage diffuse large B‐cell lymphoma of the submental region: a case report and review of the literature. (20th May 2016) - Patini, R.; Coviello, V.; Riminucci, M.; Corsi, A.; Cicconetti, A.
Abstract: Lymphomas represent the third most common group of malignant lesions in the oral cavity and maxillofacial region, following squamous cell carcinoma and salivary gland neoplasm[1, 2] . Traditionally, lymphomas are divided into two subtypes, Hodgkin lymphomas (HL) and non‐Hodgkin lymphomas (NHL)[3] . The diffuse large B‐cell lymphoma (DLBCL) is a rapidly aggressive NHL constituted by big lymphoid cells that can appear as a nodal or extra‐nodal disease; about 4% of DLBCL are initially confined to extra‐nodal sites[4] . The oral and maxillofacial region is the second most common extra‐nodal site, and half of the cases are located in Waldeyer's ring[3] . The tumour may present clinical symptoms and radiographic findings as local swelling, pain or discomfort, ulcer and bone resorption mimicking other pathologic lesions such as periodontal disease, pericoronitis, apical radiolucencies or dental abscesses[5] . We report a case of a patient with DLBCL of the submental region staged at I AE according to the Ann Arbor lymphoma staging system.